Conceptual Overview Of Shadow Economy: Socioeconomic Impact And Ramification On The Sustenance Of A Nation - G, Gopika (Innovare Journal of Business Management, 2016)
Abstract Shadow economy or informal economy is a crucial issue faced by the country in the present economic scenario. A prospering parallel economy makes the official statistics regarding unemployment,income, consumption etc inappropriate. Even a casual worker driving an unlicensed taxi at night as a second job, comes under parallel economy.